2018
DOI: 10.3390/s18041036
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Mode and Driving Activity Detection Based on Analyzing Sensor Data of Smartphones

Abstract: In this paper, we present a flexible combined system, namely the Vehicle mode-driving Activity Detection System (VADS), that is capable of detecting either the current vehicle mode or the current driving activity of travelers. Our proposed system is designed to be lightweight in computation and very fast in response to the changes of travelers’ vehicle modes or driving events. The vehicle mode detection module is responsible for recognizing both motorized vehicles, such as cars, buses, and motorbikes, and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…In the parameter optimization phase, the sensor data, including accelerometer, gyroscope, and magnetometer, are collected and labeled corresponding to the normal or abnormal driving patterns. Then, such data are passed to activity detection module (ADM) (described in [23]) to transform into two sequences of basic driving activities-containing stop (S), going straight (G), turning left (L), turning right (R)-corresponding to the long duration of activities in normal driving scenarios (representing by the window size W) and the short duration of activities in abnormal driving scenarios (representing by the window size W ). Thus, each basic driving activity is detected by ADM in a sliding data window with a specific overlapping ratio that determines the overlap between two consecutive data windows.…”
Section: Dynamic Basic Activity Sequence Matchingmentioning
confidence: 99%
See 4 more Smart Citations
“…In the parameter optimization phase, the sensor data, including accelerometer, gyroscope, and magnetometer, are collected and labeled corresponding to the normal or abnormal driving patterns. Then, such data are passed to activity detection module (ADM) (described in [23]) to transform into two sequences of basic driving activities-containing stop (S), going straight (G), turning left (L), turning right (R)-corresponding to the long duration of activities in normal driving scenarios (representing by the window size W) and the short duration of activities in abnormal driving scenarios (representing by the window size W ). Thus, each basic driving activity is detected by ADM in a sliding data window with a specific overlapping ratio that determines the overlap between two consecutive data windows.…”
Section: Dynamic Basic Activity Sequence Matchingmentioning
confidence: 99%
“…. , n. In our previous work [23], it has been shown that in the normal driving scenarios, the optimal window size for accurately identifying basic activities of car and motorcycle drivers usually ranges from 4 to 6 s. Hence, in the later experiments, W will be tested in this range.…”
Section: Dynamic Basic Activity Sequence Matchingmentioning
confidence: 99%
See 3 more Smart Citations